Produksi Enzim Selulase Dan Xilanase Dari Eupenicillium Javanicum Dengan Substrat Kulit Nanas Menggunakan Solid-State Fermentation - Ismala, Ullia Nurul; Evelyn, Evelyn; Amraini, Said Zul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The utilization of enzymes in bioprocess industry increases annually. Enzyme ability to accelerate the reaction and its biodegradability make it preferable to be utilized as catalyst. Cellulase and xylanase are ones of common enzymes that used in industries, such as pulp and paper, detergent, syrup and more. Pineapple peel waste has potential lignocellulose content to substitute pure substrate such as cellulose and xylan which is not efficient in cost. Solid-state fermentation allows the microorganism to live in condition that suits its habitat. This research aims to investigate temperature of fermentation’s (25, 30 and 35 oC) effect on cellulase and xylanase enzyme production in solid-state and comparing the enzyme activities resulted with submerged fermentation method ones. Fermentation for enzyme production was done for 96 h and the pH of medium was adjusted at 4. Enzyme activity was obtained with DNS method using spectrophotometry visible at 540 nm. The highest enzyme activities were obtained at temperature 30 oC which resulted 0,054 U/mL for cellulase and 0,077 U/mL for xylanase.Keywords : cellulase, enzyme, solid-state fermentation, submerged fermentation, xylanase